G20: hopes and realities - Carney, Richard W. (2016)
Many see recent agreements struck by G20 nations as a sign of the organisation’s effectiveness and a source of optimism for future international cooperation. However, there are important reasons to remain skeptical of countries’ willingness to abide by such agreements.